Relationship Between Job Satisfaction and Employee Retention: Evidence from an Information Technology Company in the Philippines - Alvin Francis Rommel M Molina; Pamela C Sangil; Lyle Anthony Jowill G Villas; Ravenna M Dela Cruz; Len P Macariola; Hyacinth A Crisostomo; Christian D Lleno; Jesus P Briones (Research Synergy Foundation Press, 2025)
Job satisfaction is critical to employee retention, particularly in the information technology (IT) industry. This study examines the relationship between job satisfaction and employee retention in an IT company in the Philippines. Using a descriptive-correlational research design, data were gathered from 99 IT professionals from an IT company using a convenience sampling technique. An adapted questionnaire formatted in Google Forms was used and distributed through email and Messenger to the respondents from January 29 to 31, 2025. Using Jamovi statistical software, data were analyzed using frequency, percentage, weighted mean, and Pearson’s correlation analysis. Findings revealed that employees are generally satisfied with working with an IT company, contributing to their retention. The findings further revealed that compensation, career advancement opportunities, and supervisory support had the strongest correlations with employee retention, confirming that financial stability, growth prospects, and effective leadership play critical roles in workforce sustainability. Although workplace relationships and job content contributed positively to job satisfaction, their impact on retention was relatively weaker, indicating that either social bonds or the nature of work may not entirely prevent employee turnover. The proposed strategies by the researchers are suggested as a guide to further improve job satisfaction and employee retention in the subject IT company. This study can be a reference for IT companies and other organizations with highly skilled workforces that prioritize employee satisfaction and adopt holistic retention strategies that include financial and career advancement possibilities